Restriction of 16S-23S intergenic rDNA for diversity evaluation of Azospirillum amazonense isolated from different Brachiaria spp. - Reis Junior, Fábio Bueno dos; Reis, Verônica Massena; Teixeira, Kátia Regina dos Santos (Pesquisa Agropecuaria Brasileira, 2006)
The aim of this work was to study the intra-specific diversity of Azospirillum amazonense isolates and to establish possible influences of different Brachiaria spp. and edaphoclimatic conditions. The characterization of the diversity among the isolates of A. amazonense studied was conducted using restriction analysis of the 16S-23S rDNA intergenic spacer region. The evaluated strains were separated in two groups, defined at 56% of similarity. Brachiaria spp. showed effects on strain diversity. Most part of the isolates from B. decumbens and B. brizantha are inserted in the first group, while B. humidicola isolates concentrate in the second group.